Reappearing Characters in Nineteenth-Century French Literature Authorship, Originality, and Intellectual Property - Paraschas, Sotirios (Palgrave Studies in Modern European Literature, 2018)
This book examines the phenomenon of the reappearance of characters in nineteenth-century French fiction. It approaches this from a hitherto unexplored perspective: that of the twin history of the aesthetic notion of originality and the legal notion of literary property. While the reappearance of characters in the works of canonical authors such as Honoré de Balzac and Émile Zola is usually seen as a device which transforms the individual works of an author into a coherent whole, this book argues that the unprecedented systematisation of the reappearance of characters in the nineteenth century has to be seen within a wider cultural, economic, and legal context. While fictional characters are seen as original creations by their authors, from a legal point of view they are considered to be 'ideas' which are not protected and can be appropriated by anyone. By co-examining the reappearance of characters in the work of canonical authors and their reappearances in unauthorised appropriations, such as stage adaptations and sequels, this book discusses a series of issues that have shaped our understanding of authorship, originality, and property.